Sustainability of the Bulgarian food processing industry - Nadya Kostadinova; Nadezhda Petrova; Georgi Aleksiev (The Central European Review of Economics and Management (CEREM), 2019)
Bulgarian agricultural sector underwent a transformation during the last decade of the 20th century, and its economic impact has lessened as a result. After the accession of the country to the European Union in 2007 Bulgarian agricultural product had uninterrupted access to the common market and most producers has oriented their production towards it. As a result Bulgarian food processing industry was put under great stress, due to its supply chain being greatly compromised.Aim: To investigate the sustainability of the functioning and development of the food processing industry in Bulgaria. In order to achieve this goal, the following tasks are solved: - to analyze the state and development of Bulgaria food industry; - to examine the problems and prospects for its sustainable functioning. Design / Research methods: The methods used to solve the tasks are: analysis and synthesis, systematic and structural approach, statistical calculations. Conclusions / findings: The expectations of the study are that both positive and negative trends in the sustainable functioning of the food processing industry in Bulgaria will be identified. Originality / value of the article: The prospects for the sustainable development of the food processing industry are in direct correlation and dependence not just on the opportunities for development of foreign markets as a result of the liberalization and globalization of trade, but also on the preservation of its positions in our national market.
Keywords: 330